(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Waste management incorporates technological, climatic, environmental, and demographic concerns. Socio economic, legal aspects. Traditional methodologies struggle to analyze, predict, and enhance such complex linear processes. Artificial intelligence (AI) tools can help tackle solid waste management (MSWM) concerns.AI solves obscure problems, learns from mistakes, and manages uncertainty and incomplete facts. Although much research has been done in this field, few review studies have evaluated AI’s potential in MSWM. This research examines MSWM AI models and approaches, application areas, performance factors, and software platforms used to construct such models.AI uses in MSWM are also mentioned. This document offers AI models and ideas for organic waste management and deployment, as well as reporting output criteria for implementing these frameworks.